2016
DOI: 10.1111/gbb.12308
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohypoparathyroidism type I‐b with neurological involvement is associated with a homozygous PTH1R mutation

Abstract: Pseudohypoparathyroidism type 1b (PHP1b) is characterized by hypocalcemia, hyperphosphatemia, increased levels of circulating parathyroid hormone (PTH), and no skeletal or developmental abnormalities. The goal of this study was to perform a full characterization of a familial case of PHP1b with neurological involvement and to identify the genetic cause of disease. The initial laboratory profile of the proband showed severe hypocalcemia, hyperphosphatemia and normal levels of PTH, which was considered to be com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…This interpretation is consistent with the hypothesis that the R186H mutation in vivo causes a selective deficiency in responsiveness to endogenous PTH but not PTHrP. (19) Somewhat surprisingly, we found that the PTH1R-R186H mutant exhibited a more significant reduction in cAMP signaling response potency to PTHrP than to PTH . The reason for this apparent change in the relative impact of the receptor mutation on the interaction with the C-terminally truncated PTH and PTHrP(1-28) fragment peptides, as compared to the relative impact seen with the intact PTH and PTHrP (1-36) peptides, is not clear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This interpretation is consistent with the hypothesis that the R186H mutation in vivo causes a selective deficiency in responsiveness to endogenous PTH but not PTHrP. (19) Somewhat surprisingly, we found that the PTH1R-R186H mutant exhibited a more significant reduction in cAMP signaling response potency to PTHrP than to PTH . The reason for this apparent change in the relative impact of the receptor mutation on the interaction with the C-terminally truncated PTH and PTHrP(1-28) fragment peptides, as compared to the relative impact seen with the intact PTH and PTHrP (1-36) peptides, is not clear.…”
Section: Discussionsupporting
confidence: 92%
“…distinct patient phenotypes-a hypocalcemia/hyperphosphatemia phenotype similar to that seen pseudohypoparathyroidism type 1b (PHP1B) for R186H (19) and a skeletal/dental phenotype for V204E in which the PFE appears similar to that seen in patients with Eiken syndrome caused by other homozygous PTH1R missense mutations. (17,18,21) The structural model of the PTH1R-ligand complex shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Overlapping 4.4, 18.6 and 24.6 kb STX16 deletions and deletions involving NESP and AS that affect either GNAS A/B:TSS‐DMR alone or all four DMRs have also been reported in PHP1B families . Interestingly, the PTH receptor was not considered the candidate causative gene of PHP until recent confirmation demonstrating it as a cause of familial PHP1B in one family …”
Section: Introductionmentioning
confidence: 99%
“…Pseudohypoparathyroidism (PHP) is an heterogeneous group of disorders characterised by hypocalcaemia and hyperphosphataemia resulting from end-organ resistance to parathyroid hormone (PTH) [1][2][3][4][5][6][7][8][9]. It is a rare disease with an estimated prevalence worldwide of approximately 7.9 cases per million [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since parathyroid action is only affected at the renal proximal tubule level, some individuals are asymptomatic and may show only mild elevation of PTH as evidence of hormone resistance [2,10,11,14]. However, at some point, most patients present with hypocalcaemia and develop symptoms such as tetany, muscle spasms or even seizures [2,5,11]. No deletion in the STX16 region (upstream of the GNAS cluster) was detected.…”
Section: Introductionmentioning
confidence: 99%